2020
DOI: 10.21079/11681/37259
|View full text |Cite
|
Sign up to set email alerts
|

Obstacle detection and quantification for vehicle mobility in winter conditions

Abstract: Recently, the focus for military operations has shifted from the desert to cold climates, causing a corresponding shift in the military's need to better understand the mobility of our current vehicle fleet in these areas. Therefore, this work investigated the effects of winter conditions on military vehicle mobility. The main objective was to detect obstacles on the scene. This study developed and tested a method for automatic obstacle detection in the digital elevation model of a scene. The method detects sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…A number of methods were investigated, including edge detection and texture detection. As part of this project, Vecherin et al (2020) found that the texture method generated better results than the edge-detection method, allowing the detection of snow-covered obstacles with fewer false positives. It developed an additional algorithm to determine the probability of false positives.…”
Section: Figures and Tablesmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of methods were investigated, including edge detection and texture detection. As part of this project, Vecherin et al (2020) found that the texture method generated better results than the edge-detection method, allowing the detection of snow-covered obstacles with fewer false positives. It developed an additional algorithm to determine the probability of false positives.…”
Section: Figures and Tablesmentioning
confidence: 99%
“…It developed an additional algorithm to determine the probability of false positives. Vecherin et al (2020) fully describes the obstacle detection algorithms.…”
Section: Figures and Tablesmentioning
confidence: 99%